A risk augmented mincer earnings equation? Taking stock - Joop Hartog (Institute for the Study of Labor (IZA), 2009)
We survey the literature on the Risk Augmented Mincer equation that seeks to estimate the compensation for uncertainty in the future wage to be earned after completing an education. There is wide empirical support for the predicted positive effect of wage variance and the negative effect of wage skew. We discuss robustness of the findings across specifications, potential bias from unobserved heterogeneity and selectivity and consider the core issue of students' information on benefits from education.
urn:nbn:de:101:1-200910141180
Keywords: J31; D8; 330; Human capital; earnings function; risk; Bildungsverhalten; Entscheidung bei Unsicherheit; Einkommensfunktion; Schätzung; USA